Problematics of Human Resources Development in Improving The Quality of Education in Madrasah - Muslimatun Evania Rika; Subiyantoro Subiyantoro (Journal of Educational Management Research, 2022)
The aims of this research are; 1) how to implement human resource management in career development at MI Ma'arif Giriloyo; 2) how to assess human resource management at MI Ma'arif Giriloyo. This study was conducted with a qualitative approach with the type of research, namely case studies. The critical informants of this research concern the director, teacher, and staff of MI Ma'arif Giriloyo. Data collection techniques in this study are in the form of interviews, observations, and documentation. Data collection, observation, presentation, and conclusion are data analysis techniques used in this study. The conclusions of this study include the implementation, monitoring, and evaluation of human resource management at MI Ma'arif Giriloyo, namely: 1) the development and development of professional and spiritually oriented guidance, namely observations to be liked to improve the quality of human resources According to professions that include a spiritual approach: more many studies in titles, meetings, assignments, driving, socialization or seminars; 2) monitoring and evaluation carried out by Ma'arif Giriloyo by leading and knowing the history of HR which includes monitoring and evaluating the performance of teachers and education staff. Teacher Performance History Monitoring and Evaluation System. In addition, career development teachers carry out missions at the end of each semester in connection with monitoring and evaluating performance with the presence of teacher learning and activities.